Online guided meditation training (Isha Kriya) improves self-reported symptoms of anxiety and depression within 2 weeks of practice—An observational study - Hariri, Sepideh; Vishnubhotla, Ramana V.; Reed, Preeti Upadhyay; Rayapuraju, Akila; Orui, Hibiki; Balachundhar, Pavitra; Sadhasivam, Senthilkumar; Subramaniam, Balachundhar (Frontiers in Psychiatry, 2022)
Introduction: Anxiety and depression have increased dramatically 2 to 3-fold with the COVID-19 pandemic. There is an urgent need for safe, cost-effective, and scalable approaches to alleviate this parallel mental health pandemic. Meditation has previously been shown to reduce stress, anxiety, and depression symptoms. Furthermore, online delivery of mind-body interventions will be impactful in addressing disparities in access to mental healthcare. In this observational pilot study, we investigate the impact of a digitally delivered guided meditation followed by daily practice on symptoms of anxiety and depression. Methods: Initially, 57 male and 202 female subjects enrolled in this study. Participants attended a webinar where they learned the Isha Kriya meditation practice. They were subsequently requested to perform the intervention daily for six weeks. Subjects were given scales to assess anxiety and depression at baseline, two weeks, four weeks, and six weeks following the training. The changes in the self-reported anxiety and depression scores were examined by the linear mixed effect models. Results: Participants completed survey responses for the following time points: baseline (n=82), week 2 (n=58), week 4 (n=37), and week 6 (n=28). During the 6 weeks of the study over 68% of subjects were compliant with their daily practice. When comparing baseline with week 2, the mean anxiety scores decreased from 25.4 to 16.8 (p < 0.01, d = 1.31). Similarly, mean depression scores decreased from 15 to 8.81 (p < 0.01, d = 0.9). The reduced scores for both anxiety and depression were maintained at weeks 4 and 6. Conclusion: This preliminary study assesses the effectiveness of online meditation training on self-reported symptoms of anxiety and depression. After two weeks of practice, those with baseline anxiety and depression showed significant improvement with a large effect size. The results from weeks 4 and 6 show sustained reduced anxiety and depression symptoms. These findings suggest that daily Isha Kriya practice could alleviate symptoms of these conditions. Future studies utilizing randomized control trials should be conducted to rigorously evaluate the benefits of this meditation practice on anxiety and depression.